2023
DOI: 10.1002/jhm.13248
|View full text |Cite
|
Sign up to set email alerts
|

Across race, ethnicity, and language: An intervention to improve advance care planning documentation unmasks health disparities

Priyanka A. Dutta,
Sarah J. Flynn,
Sandra Oreper
et al.

Abstract: BackgroundRacial and ethnic minority groups are less likely to have advance directives and living wills, despite the importance of advanced care planning (ACP) in end‐of‐life care. We aimed to understand the impact of an intervention to improve ACP documentation across race, ethnicity, and language on hospitalized patients at our institution.MethodsWe launched an intervention to improve the rates of ACP documentation for hospitalized patients aged >75 or with advanced illness defined by the International Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Dutta et al's 3 work provides an important example of the equity pitfalls of QI and illustrates the tension between a "one size fits all" imperative and a more thoughtful approach requiring time and effort to conduct equity-focused QI work. As Dutta et al 3 found, using an equity lens can provide new improvement directions. Incorporating equity into QI requires a purposeful and systemic approach starting from team creation and problem description to plan do study act (PDSA) cycles and evaluation.…”
mentioning
confidence: 99%
“…Dutta et al's 3 work provides an important example of the equity pitfalls of QI and illustrates the tension between a "one size fits all" imperative and a more thoughtful approach requiring time and effort to conduct equity-focused QI work. As Dutta et al 3 found, using an equity lens can provide new improvement directions. Incorporating equity into QI requires a purposeful and systemic approach starting from team creation and problem description to plan do study act (PDSA) cycles and evaluation.…”
mentioning
confidence: 99%